Determinants of international trade in services: "an analytical standard study for a selected sample of developing countries for the period (2000 - 2020)" - Ibrahim, Taleea; Abdulhameed , Abdulhameed (Humanities Journal of University of Zakho, 2023)
International trade in services is one of the important topics in the global economy at the present time, whether in developed or developing countries, and it has contributed to the process of economic growth and economic development, although developing countries have not benefited from this international trade in services because of challenges to their trade at the level Internal and external, this study aims to conduct a standard test of the determinants of international trade in services in selected developing countries (Brazil, Egypt, Indonesia, India, Republic of Korea, Morocco, Malaysia, Pakistan, Philippines, Saudi Arabia, Turkey, Vietnam), for the period 2000 - 2020 The study adopted a tabular data analysis with the use of the PMG model in the ARDL environment in the determinants of international trade in services in selected developing countries. The study concluded that population, per capita GDP, total fixed capital formation of GDP positively affects international trade in services in the long term, while inflation variables, foreign direct investment, value added of services may negatively affect trade. In the long term, this indicates that these countries have the opportunity to compete globally through the development of the services sector, provided that they are able to exploit and enhance their potential by focusing on important indicators and by removing all obstacles to international trade in services.